2002
DOI: 10.1021/bc025517+
|View full text |Cite
|
Sign up to set email alerts
|

Quantitation of the Tumor-Targeting Properties of Antibody Fragments Conjugated to Cell-Permeating HIV-1 TAT Peptides

Abstract: Human monoclonal antibodies are promising agents for the development of more selective anticancer therapeutics. However, the tumor-targeting efficiency of most anticancer antibodies is severely limited by their poor penetration into the tumor mass. Recent studies have shown that a peptide derived from the HIV TAT protein could improve the distribution of cytoplasmic reporter proteins when administered systemically as fusion proteins or cross-linked chimeras. In this article, we tested by quantitative biodistri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
105
0
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(111 citation statements)
references
References 41 publications
5
105
0
1
Order By: Relevance
“…Much effort has been put into improving the cell uptake of antibodies coupled to various CPPs since the tumor-targeting efficiency of most anticancer antibodies is severely limited by their poor penetration into the tumor mass [68]. As already discussed in a previous review [69], the coupling of cell specific antibodies to CPPs did increase their cellular internalization in vitro as expected [70].…”
Section: Problems and Limitations Of Cpps For Drug Delivery In Vivomentioning
confidence: 77%
See 1 more Smart Citation
“…Much effort has been put into improving the cell uptake of antibodies coupled to various CPPs since the tumor-targeting efficiency of most anticancer antibodies is severely limited by their poor penetration into the tumor mass [68]. As already discussed in a previous review [69], the coupling of cell specific antibodies to CPPs did increase their cellular internalization in vitro as expected [70].…”
Section: Problems and Limitations Of Cpps For Drug Delivery In Vivomentioning
confidence: 77%
“…In this study, the cell-penetrating "driving force" predominated over the specific antigen binding of the Mab fragments. Similarly, Niesner et al observed a complete loss of in vivo cellular specificity when a tumor-targeting scFv fragment was coupled to the Tat peptide [68].…”
Section: Problems and Limitations Of Cpps For Drug Delivery In Vivomentioning
confidence: 99%
“…Protein transduction is therefore a suitable method to introduce inhibitory molecules into target cells. Recent studies showed that a PTD consisting of nine D-arginine residues shows even better transduction efficiencies than the L-amino acids and that the degradation of the recombinant protein is decreased (41). Although such a PTD could be linked chemically to the peptide aptamer protein, the genetic fusion and the ease of recombinant protein production are practical advantages.…”
Section: Discussionmentioning
confidence: 99%
“…The powerful strategy of a protein transduction system has been reported previously (11,12) in studies of the protein transduction domain of HIV-1 TAT protein, which has been shown to cross biological membranes efficiently and to promote delivery of peptides and proteins into cells. Moreover, intracellular delivery of antibodies by chemically conjugating with TAT has been reported (13)(14)(15). We have succeeded previously in delivering TAT-fused peptide into live MIN6 cells (16).…”
mentioning
confidence: 92%